Konflik dan Ambiguitas dalam Implementasi Kebijakan Penataan Pasar Wuring di Kabupaten Sikka - Avryana V.E.F. Baso; Eusabius Separera Niron; Veronika Ruba Pena (Jayapangus Press, 2026)
This study aims to analyze the implementation dynamics of the Wuring Market restructuring policy in Sikka Regency and examine how market expansion triggers governance fragmentation, legality contestations, and the transformation of local government authority. Employing a qualitative research methodology with a case study approach, primary data were gathered through interviews with key stakeholders, while secondary data were obtained from local policy documents, media reports, and Supreme Court Decision No. 209 K/TUN/2025. Guided by Richard Matland’s Ambiguity-Conflict Model, the findings demonstrate that the implementation of the Wuring Market policy underwent a sequential transformation from administrative implementation to experimental implementation, symbolic implementation, and ultimately political implementation. This shift was driven by the expansion of market functions that outgrew the initial policy design, emerging governance fragmentation, legal contestations over business licensing, and reassertive authority by the local government. This study highlights the necessity for adaptive and responsive regulatory frameworks in managing local economic spaces. Local governments should look beyond initial interventions and proactively anticipate spatial dynamics to prevent institutional conflicts. Theoretically, this article contributes to policy implementation literature by demonstrating how successful community-based programs can outgrow their original policy design and reshape the implementation environment on the ground.